Method for preparing modified perovskite material by using MXene and graphdiyne

By using the dual -interface passivation method of MXENE and graphite in the solar battery of perovskite, the performance reduction problem caused by excessive PB in the perovskite solar cell solar cells is solved, and the effect of improving photoelectric conversion efficiency and reducing stagnation effects is achieved.

CN119343016APending Publication Date: 2025-01-21INST OF CHEM CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310882046.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the prior art, perovskite solar cells often leave abundant residual Pb during the preparation process, resulting in a significant reduction in device performance and no effective method of treating residual Pb ions was found.

Method used

A dual-interface passivation method is used to passivate the surface of the perovskite film substrate using MXene and graphyne respectively to fix the residual Pb ions on the surface of the perovskite film substrate.

Benefits of technology

It effectively reduces Pb residue on the surface of perovskite solar cells, reduces non-radiative recombination, improves material quality, extends carrier lifetime, increases photoelectric conversion efficiency from 22.72% to 24.86%, and reduces hysteresis effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343016A_ABST
    Figure CN119343016A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a modified perovskite material by using MXene and graphdiyne, and the method comprises the steps: (1) coating one surface of a perovskite thin film substrate with an MXene material solution, carrying out plasma treatment, and passivating the lower interface of the perovskite thin film substrate; and (2) coating the other surface of the perovskite thin film substrate with a graphdiyne solution to prepare the modified perovskite material. In the method disclosed by the invention, Pb residues are less on the surface of the modified perovskite material, and non-radiative recombination is greatly reduced; the modified perovskite material is high in quality, and surface defects generated in the preparation process are reduced; the average carrier lifetime is far longer than that of an original perovskite thin film; the photoelectric conversion efficiency is improved from 22.72% to 24.86% (improved by 9.4%), and meanwhile, the hysteresis effect is obviously reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite thin films, and in particular to a method for preparing a modified perovskite material by utilizing MXene and graphyne. Background Art

[0002] Organic metal halide perovskites have excellent optoelectronic properties and are widely used in various optoelectronic devices. Among them, perovskite solar cells are particularly eye-catching, with a photoelectric conversion efficiency of 26.0%, close to the most advanced crystalline silicon cells.

[0003] When preparing high-efficiency perovskite solar cells using a two-step approach, a Pb-containing perovskite film is usually used as the active absorber layer. When preparing the film, excess Pb is usually used in the precursor to promote the crystallization of the perovskite, reduce halide vacancies, and promote the formation of α-phase crystals. However, this process usually leaves abundant residual Pb on the surface of the perovskite film, which can significantly degrade the device performance: the Pb ions at the perovskite / carrier transport layer interface are key catalytic sites and can induce perovskite decomposition during operation. At the same time, Pb-rich Pb ions are more easily formed in the unreacted residual crystalline Pb ions. 0 The holes in the perovskite solar cell are the centers of non-radiative recombination, which will lead to a decrease in open circuit voltage and fill factor. However, no effective method for treating residual Pb ions has been found in the prior art. Summary of the invention

[0004] In order to improve the above technical problems, the present invention provides a method for preparing a modified perovskite material using MXene and graphyne. The method adopts a double-interface passivation method to passivate the surface of the perovskite film substrate by MXene and graphyne, respectively, and fix the residual Pb ions on the surface of the perovskite film substrate in the perovskite crystal, so as to solve the problem of excessive Pb in perovskite solar cells.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing a modified perovskite material using MXene and graphyne, the method comprising:

[0007] (1) Coating a MXene material solution on one side of a perovskite film substrate and performing plasma treatment to passivate the lower interface of the perovskite film substrate.

[0008] According to an embodiment of the present invention, the transition metal in the MXene material is selected from Ti, which includes a compound having a chemical formula shown in formula (I):

[0009] Ti n+1 C n T x(I)

[0010] Wherein, n=1, 2, 3, T is a terminal oxygen, fluorine atom or hydroxyl group, and x represents the number of functional groups.

[0011] According to an embodiment of the present invention, the MXene material is Ti2CT x 、Ti3C2T x 、Ti4C3T x When the MXene material is a mixture, it can be mixed in any proportion, and T and x have the above meanings.

[0012] According to an embodiment of the present invention, the MXene material is a nanomaterial, and the particle size of the MXene material is 500nm-10μm.

[0013] According to an embodiment of the present invention, the MXene material solution is an aqueous solution of MXene material, and the concentration of the MXene material solution is 0.01-0.5 mg / mL, preferably 0.05-0.4 mg / mL, for example, 0.05 mg / mL, 0.1 mg / mL, 0.2 mg / mL, 0.3 mg / mL, 0.4 mg / mL.

[0014] According to an embodiment of the present invention, in step (1), spin coating may be used, for example, the MXene coating speed is 1500-4000 rpm, for example, 3000 rpm.

[0015] According to an embodiment of the present invention, in step (1), the atmosphere of the plasma treatment is an oxygen atmosphere.

[0016] According to an embodiment of the present invention, in step (1), the power of the plasma treatment is 40-60 W, for example, 50 W, and the time is 2-10 min, for example, 5 min.

[0017] According to an embodiment of the present invention, the method further comprises step (2): coating the graphyne solution on the other surface of the perovskite film substrate to prepare the modified perovskite material.

[0018] According to an embodiment of the present invention, the graphyne is a nanomaterial.

[0019] According to an embodiment of the present invention, the graphyne solution is a chlorobenzene solution of graphyne; the concentration of the graphyne solution is 0.01-0.5 mg / mL, for example, 0.01 mg / mL, 0.05 mg / mL, 0.1 mg / mL, 0.2 mg / mL, 0.3 mg / mL, 0.4 mg / mL, 0.5 mg / mL.

[0020] According to an embodiment of the present invention, the coating speed of the nano-graphene solution is 3000-5000 rpm, such as 4000 rpm, and the coating time is 20-40s, such as 30 seconds.

[0021] According to an embodiment of the present invention, the perovskite film substrate is a tri-cation CsFAMA perovskite film.

[0022] According to an embodiment of the present invention, the method further comprises preparing a perovskite thin film substrate, comprising:

[0023] (S1) dissolving PbI2 and a compound containing Cs in an organic solvent, coating the prepared mixed solution on a substrate, and performing annealing treatment to obtain a PbI2 thin film;

[0024] (S2) Spin-coating a mixed ammonium salt solution containing MA and FA onto the surface of the PbI2 thin film layer, and performing annealing treatment to obtain a perovskite thin film substrate.

[0025] According to an embodiment of the present invention, in step (S1), the material of the substrate is not particularly limited as long as it can carry the coating liquid. The substrate is, for example, a glass substrate, a polyamide film substrate, a polyimide film substrate, an electron transport layer, etc., and is also, for example, a SnO2 electron transport layer.

[0026] According to an embodiment of the present invention, in step (S1), the compound containing Cs is, for example, CsI.

[0027] According to an embodiment of the present invention, in step (S1), the Cs-containing compound is 2%-6% of the amount of PbI2 substance, preferably 3%-5%.

[0028] According to an embodiment of the present invention, in step (S1), the organic solvent is selected from at least one of DMF and DMSO.

[0029] According to an embodiment of the present invention, in step (S1), the concentration of PbI2 in the organic solvent is 0.5-2 mg / μL, preferably 0.5-1 mg / μL.

[0030] According to an embodiment of the present invention, in step (S1), the speed of coating the mixed solution is 1000-3000 rpm, such as 1500 rpm, and the coating time of the mixed solution is 10-90s, preferably 20-40s, such as 30s.

[0031] According to an embodiment of the present invention, in step (S1), the annealing temperature is 50-100° C., preferably 60-80° C.; the annealing time is 1-20 min, preferably 1-10 min.

[0032] According to an embodiment of the present invention, in step (S2), the mixed ammonium salt is selected from FAI, and is also selected from one or two of MACl and MABr, for example, a mixture of FAI, MACl and MABr. Preferably, in the mixed ammonium salt, MACl is 30%-60% of the amount of FAI substance, preferably 40%-50%; and MABr is 1%-8% of the amount of MABr substance, preferably 2%-5%.

[0033] According to an embodiment of the present invention, in step (S2), the mixed ammonium salt solution is mixed ammonium salt dissolved in isopropanol.

[0034] According to an embodiment of the present invention, in step (S2), the annealing temperature is 140-200° C., preferably 150-180° C.; the annealing time is 8-30 min, preferably 10-20 min.

[0035] As an exemplary embodiment of the present invention, the method for preparing the modified perovskite material specifically includes:

[0036] (K1) coating a MXene material solution on a glass substrate and performing a plasma treatment;

[0037] (K2) dissolving PbI2 and a compound containing Cs in an organic solvent, coating the prepared mixed solution on the film prepared in step K1, and annealing to obtain a PbI2 film;

[0038] (K3) spin coating a mixed ammonium salt solution containing MA and FA onto the surface of the PbI2 thin film layer, and performing annealing treatment to obtain a perovskite thin film substrate;

[0039] (K4) coating the graphyne solution on the other surface of the perovskite film substrate to prepare the modified perovskite material.

[0040] The present invention provides a modified perovskite material prepared by the above method.

[0041] The present invention also provides application of the modified perovskite material in solar cells.

[0042] The present invention also provides a solar cell, which comprises the modified perovskite material.

[0043] According to an embodiment of the present invention, the solar cell comprises ITO conductive glass, an electron transport layer, the above-mentioned modified perovskite material, a hole transport layer and an electrode in sequence.

[0044] Preferably, the electron transport layer is a SnO2 electron transport layer.

[0045] Preferably, the hole transport layer is a Spiro-OMeTAD hole transport layer.

[0046] Preferably, the electrode is, for example, a gold electrode.

[0047] The present invention also provides a method for preparing the above solar cell, the method comprising:

[0048] (P1) preparing ITO conductive glass and an electron transport layer, and placing the electron transport layer on the ITO conductive glass;

[0049] (P2) coating the MXene material solution on the electron transport layer and performing plasma treatment;

[0050] (P3) dissolving PbI2 and a compound containing Cs in an organic solvent, coating the prepared mixed solution on the film prepared in step P3, and annealing to obtain a PbI2 film;

[0051] (P4) spin coating a mixed ammonium salt solution containing MA and FA onto the surface of the PbI2 thin film layer, and performing annealing treatment to obtain a perovskite thin film substrate;

[0052] (P5) coating the Graphene solution on the other surface of the perovskite film substrate;

[0053] (P6) placing a hole transport layer on the film prepared in step P5;

[0054] (P7) Placing an electrode on the hole transport layer to prepare the battery.

[0055] Beneficial effects of the present invention:

[0056] The present invention provides a method for preparing a modified perovskite film by performing double-interface passivation on the surface of a perovskite film substrate by using MXene and nano-graphene. The surface of the modified perovskite material has little Pb residue, and non-radiative recombination is greatly reduced; the modified perovskite material has high quality, and the surface defects generated during the preparation process are reduced; the average carrier lifetime is much longer than that of the original perovskite film; the photoelectric conversion efficiency is increased from 22.72% to 24.86% (an increase of 9.4%), and the hysteresis effect is significantly reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 Schematic diagram of the structure of the solar cell of the present invention and SEM morphology of the surface of the modified perovskite film in Example 2 (d), Comparative Example 5 (b) and Comparative Example 3 (c).

[0058] Figure 2 AFM and KPFM morphology images of the electron transport material and the modified perovskite material in Example 2 and Comparative Example 3.

[0059] Figure 3GIWAXS images of the perovskite film in Comparative Example 5 (a) and the modified perovskite film in Example 2 (b).

[0060] Figure 4 The steady-state fluorescence spectra (PL) and transient fluorescence spectra (TRPL) of the modified perovskite films in Example 2 and Comparative Examples 5, 3, and 7.

[0061] Figure 5 The forward and reverse scanning efficiency, photovoltaic performance and stability of the solar cell devices in Example 2 and Comparative Example 5 are tested. DETAILED DESCRIPTION

[0062] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0063] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0064] FAI: formamidine iodate; MACl: methylamine hydrochloride; MABr: methylamine bromide; MAI: methylamine iodate.

[0065] Comparative Examples 1-4

[0066] 1.1 Experimental conditions

[0067] The drugs PbI2, FAI, MACl and MABr were weighed at room temperature, and the ambient humidity was controlled below 40%. The SnO2 electron transport layer was spin-coated in the atmosphere, and the ambient humidity was maintained at about 40% during the annealing process. The spin coating of the perovskite and Spiro-OMeTAD hole transport layer was carried out in a nitrogen glove box, and the temperature in the glove box was controlled at 25°C, the moisture content was ≤0.1ppm, and the oxygen content was ≤0.1ppm. The perovskite was annealed in air, and the ambient humidity was controlled at about 40%. The double interface passivation treatment was carried out in the glove box.

[0068] 1.2 Preparation of perovskite solar cells

[0069] ITO glass cleaning: clean with detergent, rinse with water, ultrasonically treat in pure water, acetone and isopropanol for 15 minutes in sequence. Treat in oxygen plasma cleaner for 5 minutes before use.

[0070] Preparation of electron transport layer: dilute the SnO2 colloidal dispersion, the volume ratio of SnO2 and ultrapure water is 2:5, spin-coat in air (3000rpm, 30s), and then anneal (150℃, 30min). After annealing, an electron transport layer film is obtained.

[0071] MXene passivation treatment: Spin-coat a certain concentration of Ti3C2Cl on the prepared electron transport layer x Aqueous solution, in which the specific Ti3C2Cl x The concentration of the aqueous solution is shown in Table 1 below. The spin coater was set to 3000 rpm for 30 seconds to obtain a thin film covered with MXene. The film was treated in an oxygen plasma cleaner for 5 minutes before the perovskite was spin-coated.

[0072] Preparation of tricationic CsFAMA perovskite film (two-step method): (1) Transfer the electron transport layer sample to the glove box for operation. Dissolve PbI2 (691.5 mg) and CsI (5% of the amount of PbI2) powder in DMF (900 μL) and DMSO (100 μL). Set the spin coater parameters to (1500 r / min, 30 s), take PbI2 solution (40 μL) and spin coat it on the electron transport layer, and then anneal at 70 ° C in the glove box for 1 min to obtain a bright yellow PbI2 film. (2) Weigh FAI (90 mg), MACl (40% of the amount of FAI), and MABr (2% of the amount of FAI), add isopropanol (1000 μL) and dissolve for 30 min (operate in the glove box), and ultrasonically dissolve for 30 min. The spin coater was set to (2000 r / min, 30 s), and the mixed ammonium salt solution was added to the surface of the PbI2 film by dynamic spin coating, and then transferred to the air for annealing at 150°C for 15 min (keeping the air humidity at about 40%) to finally obtain a perovskite film.

[0073] Nano-graphene passivation treatment: 0 mg / mL nano-graphene chlorobenzene solution was spin-coated on the prepared perovskite film, and the spin coater was set to 4000 rpm for 30 seconds to obtain a film covered with nano-graphene.

[0074] Preparation of hole transport layer: Spiro-OMeTAD (72.3 mg) was dissolved in 1 mL of chlorobenzene, and Li-TFSI solution (17.5 μL) and TBP solution (29 μL) were added. 40 μL of the solution was added dropwise and quickly rotated to prepare a hole transport layer film, and then the prepared sample was transferred to a desiccator for oxidation for 24 hours.

[0075] Electrode preparation: The sample was transferred to a vacuum coating machine and -4 60nm gold was plated under Pa conditions, and the effective area of ​​the electrode was 0.04cm 2 Finally, the solar cell device structure is glass / ITO / SnO2 / MXene / perovskite / nanographene / Spiro-OMeTAD / Au.

[0076] The battery prepared in Comparative Example 3 is named MP.

[0077] Comparative Example 5

[0078] The difference between Comparative Example 5 and Comparative Example 1 is that Mxene is not added, that is, only the perovskite thin film substrate in Comparative Example 1 is used to prepare the solar cell (named as control).

[0079] Comparative Examples 6-9

[0080] The difference between Comparative Examples 6-9 and Comparative Example 5 is that the concentrations of the nano-graphene chlorobenzene solutions in Comparative Examples 6-9 are 0.01 mg / mL, 0.05 mg / mL, 0.1 mg / mL, and 0.5 mg / mL, respectively.

[0081] The battery prepared in Comparative Example 7 is named PG.

[0082] Example 1

[0083] A method for preparing a modified perovskite material using MXene and graphyne, the method comprising:

[0084] (1) Ti3C2T x The solution (concentration of 0.2 mg / mL) was spin-coated on one side of the tricationic CsFAMA perovskite film substrate, and the spin coater was set to 3000 rpm for 30 seconds, and oxygen plasma treatment was performed for 5 minutes to passivate the lower interface of the perovskite film substrate.

[0085] (2) A 0.05 mg / mL chlorobenzene solution of nano-graphene was coated on the other surface of the perovskite film substrate, and the spin coater was set to 4000 rpm for 30 seconds to prepare the modified perovskite material.

[0086] The preparation of the tricationic CsFAMA perovskite film substrate is the same as that of Comparative Example 1, except that the electron transport layer in Comparative Example 1 is replaced by a glass substrate.

[0087] Example 2

[0088] ITO glass cleaning: clean with detergent, rinse with water, ultrasonically treat in pure water, acetone and isopropanol for 15 minutes in sequence. Treat in oxygen plasma cleaner for 5 minutes before use.

[0089] Preparation of electron transport layer: dilute the SnO2 colloidal dispersion, the volume ratio of SnO2 and ultrapure water is 2:5, spin-coat in air (3000rpm, 30s), and then anneal (150℃, 30min). After annealing, an electron transport layer film is obtained.

[0090] MXene passivation treatment: spin-coat 0.2 mg mL -1 Ti3C2Cl x The aqueous solution was spin-coated at 3000 rpm for 30 seconds to obtain a thin film covered with MXene. The film was treated in an oxygen plasma cleaner for 5 minutes before spin coating of perovskite.

[0091] Preparation of tricationic CsFAMA perovskite film (two-step method): (1) Transfer the electron transport layer sample to the glove box for operation. Dissolve PbI2 (691.5 mg) and CsI (5% of the amount of PbI2) powder in DMF (900 μL) and DMSO (100 μL). Set the spin coater parameters to (1500 r / min, 30 s), take PbI2 solution (40 μL) and spin coat it on the electron transport layer, and then anneal at 70 ° C in the glove box for 1 min to obtain a bright yellow PbI2 film. (2) Weigh FAI (90 mg), MACl (40% of the amount of FAI), and MABr (2% of the amount of FAI), add isopropanol (1000 μL) and dissolve for 30 min (operate in the glove box), and ultrasonically dissolve for 30 min. The spin coater was set to (2000 r / min, 30 s), and the mixed ammonium salt solution was added to the surface of the PbI2 film by dynamic spin coating, and then transferred to the air for annealing at 150°C for 15 min (keeping the air humidity at about 40%) to finally obtain a perovskite film.

[0092] Nano-graphene passivation treatment: spin-coat 0.05 mg mL -1 The nano-graphene chlorobenzene solution was prepared by spin coating at 4000 rpm for 30 seconds to obtain a film covered with nano-graphene.

[0093] Preparation of hole transport layer: Spiro-OMeTAD (72.3 mg) was dissolved in 1 mL of chlorobenzene, and Li-TFSI solution (17.5 μL) and TBP solution (29 μL) were added. 40 μL of the solution was added dropwise and quickly rotated to prepare a hole transport layer film, and then the prepared sample was transferred to a desiccator for oxidation for 24 hours.

[0094] Electrode preparation: The sample was transferred to a vacuum coating machine and -4 60nm gold was plated under Pa conditions, and the effective area of ​​the electrode was 0.04cm 2 Finally, the solar cell device structure is glass / ITO / SnO2 / MXene / perovskite / nanographene / Spiro-OMeTAD / Au, and the prepared cell is named MPG.

[0095] The performance of the batteries prepared in Comparative Examples 1-9 is shown in Table 1 and Table 2 below.

[0096] Table 1 MXene material concentrations in comparative examples 1-5 and performance parameters of solar cells prepared therefrom

[0097]

[0098] As shown in Table 1, compared with Comparative Example 5, Ti3C2Cl x The battery with MXene added has a higher open circuit voltage V oc , filling factor FF and photoelectric conversion efficiency PCE. In contrast, the PCE of the best performing nano MXene single interface passivation device is significantly enhanced to 24.00%, V oc Higher, 1.189V, J SC The FF is 81.24% and the FF is 24.85 mA cm-2. x The optimal concentration of MXene aqueous solution is 0.2 mg mL -1 .

[0099] Table 2 Concentration of nano-graphene and performance parameters of solar cells prepared in Examples 5-9

[0100]

[0101] As shown in Table 2, the device with the addition of nano-graphene has a higher open circuit voltage V oc , fill factor FF and photoelectric conversion efficiency PCE. The PCE of the best performing Control device is 22.72%, V OC is 1.173V, J SC 24.81 mA cm -2 , FF is 78.05%; in contrast, the PCE of the device using nano-graphene single interface passivation is significantly enhanced to 23.98%, V oc Higher, 1.185V, J SC The optimal concentration of nano-graphene is 0.05 mg mL -1 .

[0102] Test Example 1 Characterization of Modified Perovskite Film (Material)

[0103] Figure 1 (a) is a schematic diagram of the structure of the solar cell of the present invention and SEM morphology images of the surface of the modified perovskite film in Example 2 (d), Comparative Example 5 (b) and Comparative Example 3 (c).

[0104] The perovskite film in Comparative Example 5 has needle-shaped PbI2 grains surrounding the perovskite grains. In contrast, after the introduction of MXene on the SnO2 electron transport layer (Comparative Example 3), the size of the perovskite crystals increased from 1.47μm to 2.41μm, indicating that MXene is beneficial to the growth of the perovskite film. We believe that the large grains produced by the combination of MXene and PbI2 in the precursor solution with Pb-Cl are beneficial to the transport of carriers to the ITO electrode. The strong Pb-Cl bond can promote the full reaction of the PbI2 film with the ammonium salt, which is beneficial to the formation of α-phase perovskite. In addition, the film spin-coated with nano-graphene has a uniform surface morphology without pinholes, and the crystal size increases to 2.56μm (such as Figure 1 d). In addition to the good film morphology, the crystallinity of the perovskite film is also significantly improved. These results indicate that MXene and nano-graphene can combine with PbI2 in perovskite to slow down the nucleation rate of the intermediate phase and improve the surface uniformity.

[0105] Figure 2 AFM and KPFM morphology images of the electron transport layer and the modified perovskite film in Example 2 and Comparative Example 3, wherein Figures a and b are AFM images of the modified perovskite film in Comparative Example 3 and Example 2, respectively; Figures c and d are KPFM morphology images of the modified perovskite film in Comparative Example 3 and Example 2, respectively. Atomic force microscopy (AFM) characterization and Kelvin probe force microscopy (KPFM) also reveal the coherent growth from bottom to top of larger grain sizes. The stepped edges on the surface in Comparative Example 3 and Example 2 indicate the formation of highly crystallized perovskite. For the perovskite film in Comparative Example 3, surface defects exacerbate the roughness and potential distribution of the perovskite surface. In contrast, the surface roughness and potential changes of the modified perovskite material (film) prepared by the present invention are significantly reduced. Through the linear scan of the height mode of MXene induction in a specific area (i.e., Comparative Example 3) and large particles treated with MXene and nano-graphene simultaneously (i.e., Example 2), the fluctuation of the film (material) in Example 2 is about 10-20nm, which is lower than that in Comparative Example 3 (40-60nm), indicating that the surface defects are effectively passivated by nano-graphene, and the surface is smoother. After nano-graphene treatment, the root mean square roughness (RMS) drops from 40.8nm to 29.1nm. Similarly, the potential line scan of large particles in a specific area of ​​the modified perovskite material of Comparative Example 3 and the modified perovskite material of Example 2 also has the same trend. The potential change of Example 2 (10-20mV) is much lower than that of Comparative Example 3 (30-40mV). Based on the above results, we can infer that MXene mainly increases the grain size of perovskite to enhance bottom contact and electron transport. Nano-graphene suppresses the surface defects caused by the spin coating process, which will form a smoother surface and reduce non-radiative recombination.

[0106] Test Example 2 Carrier Transport Characterization

[0107] Figure 4 Steady-state fluorescence spectra (PL) (a) and transient fluorescence spectra (TRPL) (b, c) of the modified perovskite films in Example 2 and Comparative Examples 5, 3, and 7. The carrier lifetime of the perovskite film is analyzed by steady-state fluorescence spectra (PL) and transient fluorescence spectra (TRPL). Figure 4 a shows the PL of the film under 485 nm excitation. Compared with Comparative Example 5, the modified perovskite film of Example 2 shows the highest PL peak intensity, indicating that the double interface passivation effectively removes the residual Pb. Figure 4 b shows that the average carrier lifetime of the modified perovskite film is longer than that of the perovskite film of Comparative Example 5 (10.71 μs vs 1.72 μs).

[0108] Test Example 3 Battery Performance Characterization

[0109] The structure of the perovskite solar cell in Example 2 is ITO / SnO2 / MXene / perovskite / NanoGDY / Spiro-OMeTAD / Au, named MPG device. Figure 5 The forward and reverse scanning efficiency, photovoltaic performance and stability test of the solar cell device in Example 2 and Comparative Example 5 are shown in FIG. Figure 5 As shown in a.

[0110] Combined with Table 1, the MPG device has a higher open circuit voltage V oc , fill factor FF and photoelectric conversion efficiency PCE. Compared with comparative example 5, the PCE of the MPG device of the present invention is significantly enhanced to 24.86%, V oc Higher, 1.203V, J SC 25.16mAcm -2 , FF is 82.14%. It can be seen that the modified perovskite film of the present invention can improve the device efficiency by 9.4% and significantly reduce the hysteresis.

[0111] The MPG devices also showed stronger stability in the aging test: after being stored in the dark in air with a humidity of 20 RH% for more than 1464 hours, the PCE of the solar cells of Comparative Example 5 and Example 2 retained 78% and 92% of their initial values, respectively ( Figure 5 c); Under continuous heating (85°C) for more than 1000 h in a N2 glove box, the PCE of the solar cells of Comparative Example 5 and Example 2 retained 43% and 80% of their initial values, respectively ( Figure 5 b).

[0112] Table 3

[0113]

[0114] In the present invention, 0.2 mg / mL Ti3C2Cl x MXene and 0.05mg / mL nanographene chlorobenzene solution can basically completely or partially controllably remove the unstable Pb at the interface, without damaging the perovskite film by adjusting the surface properties. This improves the quality of the perovskite film, greatly reduces the defects of the perovskite film, and inhibits charge recombination. Therefore, devices based on modified perovskite films show excellent optoelectronic properties and stability.

[0115] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a modified perovskite material using MXene and graphyne, characterized in that: The method comprises: (1) Coating a MXene material solution on one side of a perovskite film substrate and performing plasma treatment to passivate the lower interface of the perovskite film substrate.

2. The method according to claim 1, characterized in that The transition metal in the MXene material is selected from Ti, which includes a compound having a chemical formula shown in formula (I): Ti n+1 C n T x (I) Wherein, n=1, 2, 3, T is a terminal oxygen, fluorine atom or hydroxyl group, and x represents the number of functional groups. Preferably, the MXene material is Ti2CT x 、Ti3C2T x 、Ti4C3T x One or any of the following. Preferably, the MXene material solution is an aqueous solution of MXene material, and the concentration of the MXene material solution is 0.01-0.5 mg / mL.

3. The method according to claim 1 or 2, characterized in that: The method further comprises step (2): coating the graphyne solution on the other surface of the perovskite film substrate to prepare the modified perovskite material. Preferably, the graphyne solution is a chlorobenzene solution of graphyne; the concentration of the graphyne solution is 0.01-0.5 mg / mL.

4. The method according to any one of claims 1 to 3, characterized in that: The perovskite film substrate is a tri-cation CsFAMA perovskite film. Preferably, the method further comprises preparing a perovskite thin film substrate, comprising: (S1) dissolving PbI2 and a compound containing Cs in an organic solvent, coating the prepared mixed solution on a substrate, and performing annealing treatment to obtain a PbI2 thin film; (S2) Spin-coating a mixed ammonium salt solution containing MA and FA onto the surface of the PbI2 thin film layer, and performing annealing treatment to obtain a perovskite thin film substrate.

5. The method according to any one of claims 1 to 4, characterized in that: In step (S1), the compound containing Cs is CsI. Preferably, in step (S1), the Cs-containing compound is 2%-6% of the amount of PbI2 substance. Preferably, in step (S1), the organic solvent is selected from at least one of DMF and DMSO. Preferably, in step (S1), the concentration of PbI2 in the organic solvent is 0.5-2 mg / μL. Preferably, in step (S1), the annealing temperature is 50-100°C.

6. The method according to any one of claims 1 to 5, characterized in that: In step (S2), the mixed ammonium salt is selected from FAI, and is also selected from one or two of MACl and MABr; In step (S2), the annealing temperature is 140-200° C., and the annealing time is 8-30 min.

7. The modified perovskite material prepared by the method according to any one of claims 1 to 6.

8. Use of the modified perovskite material according to claim 7 in solar cells.

9. A solar cell, characterized in that: The battery comprises the modified perovskite material according to claim 7. Preferably, the solar cell comprises ITO conductive glass, an electron transport layer, a modified perovskite material, a hole transport layer and an electrode in sequence.

10. The method for preparing a solar cell according to claim 9, characterized in that: The method comprises: (P1) preparing ITO conductive glass and an electron transport layer, and placing the electron transport layer on the ITO conductive glass; (P2) coating the MXene material solution on the electron transport layer and performing plasma treatment; (P3) dissolving PbI2 and a compound containing Cs in an organic solvent, coating the prepared mixed solution on the film prepared in step P3, and annealing to obtain a PbI2 film; (P4) spin coating a mixed ammonium salt solution containing MA and FA onto the surface of the PbI2 thin film layer, and performing annealing treatment to obtain a perovskite thin film substrate; (P5) coating the graphyne solution on the other surface of the perovskite film substrate; (P6) placing a hole transport layer on the film prepared in step P5; (P7) Placing an electrode on the hole transport layer to prepare the battery.